Pengaruh Penempatan Tenaga Kerja Pegawai Terhadap Kinerja Pegawai (Indo-MathEdu Intellectuals Journal, 2024)
Manpower placement is a series of processes after recruitment and selection to determine positions in accordance with their abilities in order to complete work effectively and efficiently in accordance with what has been determined by the organization. Performance is the achievement of work results charged to employees based on experience, proficiency, sincerity, time, quantity, quality, reliability, attendance, and ability to cooperate. In the placement of manpower, knowledge and experience and ability are needed in carrying out their duties and if they are not experts who do it, there will be destruction or failure, so to achieve success in the right placement according to their expertise is needed. This research is library research and is included in the qualitative research approach. Data collection is carried out directly from various relevant literature including research articles sourced from Google Scholar. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusions. The results of data analysis show that labor placement affects employee performance. This can be seen from the responsibility of employees to work, the punctuality of coming to work and the responsibility in completing tasks at work